Parental‐genome dosage effects on the transcriptome of F1 hybrid triploid embryos of Arabidopsis thaliana. (28th November 2017) - Fort, Antoine; Tuteja, Reetu; Braud, Martin; McKeown, Peter C.; Spillane, Charles
Summary: Genomic imprinting in the seed endosperm could be due to unequal parental‐genome contribution effects in triploid endosperm tissue that trigger parent‐of‐origin specific activation and/or silencing of loci prone to genomic imprinting. To determine whether genomic imprinting is triggered by unequal parental‐genome contribution effects, we generated a whole‐genome transcriptome dataset of F1 hybrid triploid embryos (as mimics of F1 hybrid triploid endosperm). For the vast majority of genes, the parental contributions to their expression levels in the F1 triploid hybrid embryos follow a biallelic and linear expression pattern. While allele‐specific expression (ASE) bias was detected, such effects were predominantly parent‐of‐origin independent. We demonstrate that genomic imprinting is largely absent from F1 triploid embryos, strongly suggesting that neither triploidy nor unequal parental‐genome contribution are key triggers of genomic imprinting in plants. However, extensive parental‐genome dosage effects on gene expression were observed between the reciprocal F1 hybrid embryos, particularly for genes involved in defence response and nutrient reservoir activity, potentially leading to the seed size differences between reciprocal triploids. We further determined that unequal parental‐genome contribution in F1 triploids can lead to overexpression effects that are parent‐of‐origin dependent, and which are not observed in diploid or tetraploid embryos in which the parental‐genome dosage is balanced. Overall, our study demonstrates that neither triploidy nor unequal parental‐genome contribution is sufficient to trigger imprinting in plant tissues, suggesting that genomic imprinting is an intrinsic and unique feature of the triploid seed endosperm. Significance Statement: Allele‐specific transcriptome analysis of reciprocal F1 hybrid triploid embryos demonstrates that while parental‐genome dosage effects on gene expression occur, such parent‐of‐origin effects are not due to genomic imprinting. The lack of genomic imprinting in F1 triploid embryos, which have the same genotype as an F1 triploid endosperm, strongly suggests that genomic imprinting is an intrinsic and unique feature of the seed endosperm.